2004
DOI: 10.1111/j.1464-410x.2004.04607.x
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine vs placebo in the treatment of stress urinary incontinence: a four‐continent randomized clinical trial

Abstract: used to analyse the percentage changes in IEF where the stratification variable was weekly baseline IEF (IEF <14 and ≥ 14). Analysis of covariance was used to analyse I-QOL scores. RESULTSThe mean baseline IEF was 18.4/week; 55% of patients had a baseline IEF of ≥ 14. There was a significantly greater median decrease in IEF with duloxetine with placebo (54% vs 40%, P = 0.05), with comparable significant improvements in quality of life (I-QOL score increases of 10.3 vs 6.4, P = 0.007). The improvements with dul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
173
2
17

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(211 citation statements)
references
References 21 publications
14
173
2
17
Order By: Relevance
“…The published articles from these trials stated that adverse events were ascertained through nonprobing questions. [31][32][33][34] All formats of harms data presented MedDRA preferred terms. Narratives were the only format to report verbatim terms.…”
Section: Resultsmentioning
confidence: 99%
“…The published articles from these trials stated that adverse events were ascertained through nonprobing questions. [31][32][33][34] All formats of harms data presented MedDRA preferred terms. Narratives were the only format to report verbatim terms.…”
Section: Resultsmentioning
confidence: 99%
“…This was worse than those reported in the pooled analysis from the Phase 3 randomised placebocontrolled studies on a worldwide scale, which was 75%. [6][7][8][9] Interestingly a similar number of women with mixed incontinence and USI had a PGI-I score indicating improvement. This suggests that there may be a role for duloxetine in the treatment of women with mixed incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…16 Duloxetine trials suggest benefit in the treatment arm of between 49-65% and low discontinuation rates due to adverse effects (22%). [6][7][8][9] A Cochrane review reports that duloxetine significantly improved the QoL of patients with SUI. 17 The review reported that one in eight women stopped duloxetine due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations